Khwāmphưngph̨ōčhai kh̨ōng prachāchon thī mī t̨ō talāt sot thētsabān, Thētsabān Nakh̨ōn Kh̨ōn K̄æn, Čhangwat Kh̨ōn K̄æn - Sukanyā R̄ưangsuwan (Phāk Wichā Sathiti, Khana Witthayāsāt, Mahāwitthayālai Kh̨ōn K̄æn, 2004)
Research study on the satisfaction towards the Municipality fresh market of Khon Kaen Province, Northeastern Thailand.